2001
DOI: 10.1258/0022215011906975
|View full text |Cite
|
Sign up to set email alerts
|

Role of a home care team in paediatric day-case tonsillectomy

Abstract: The feasibility of paediatric day-case tonsillectomy (PDCT) depends on its safety and acceptance by parents and patients. The purpose of our retrospective study of paediatric day-case tonsillectomy was to review the role of the home care team (HCT) in improving the safety and acceptance of the procedure. Between January 1997 and June 1999, 352 consecutive children underwent day-case tonsillectomy. The notes and HCT assessment sheets were reviewed for telephone calls made by HCT or by parents, home visit by HCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
8
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
4
8
0
Order By: Relevance
“…Management of postoperative nausea and vomiting was the most common reason for conversion. Hellier et al [11] report a similar conversion incidence of 3.3% (CI 2.2-4.5%) for postoperative vomiting, consistent with other authors [13,33]. These conversion rates are far less than earlier reports of 14% [13,22], reflecting improved patient selection, surgical technique and antiemetic treatments.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Management of postoperative nausea and vomiting was the most common reason for conversion. Hellier et al [11] report a similar conversion incidence of 3.3% (CI 2.2-4.5%) for postoperative vomiting, consistent with other authors [13,33]. These conversion rates are far less than earlier reports of 14% [13,22], reflecting improved patient selection, surgical technique and antiemetic treatments.…”
Section: Discussionsupporting
confidence: 62%
“…These conversion rates are far less than earlier reports of 14% [13,22], reflecting improved patient selection, surgical technique and antiemetic treatments. Our guidelines for in-patient tonsillectomy were developed from those commonly quoted in the literature [18,29,[33][34][35]. These guidelines have remained constant throughout the 9-year study period, although criteria concerning the distance a patient lives from the hospital have been liberalized.…”
Section: Discussionmentioning
confidence: 99%
“…Stewart et al 13 found 80% were satisfied with day case while Shah et al. 14 found 96.8% satisfaction. Many patients would rather recover at home where they feel they would get a better nights sleep, nicer food and avoid MRSA.…”
Section: Discussionmentioning
confidence: 98%
“…In the UK, reported day-case surgery eligibility rates have ranged between 16 and 92 per cent. [18][19][20][21][22][23] Internationally, individual unit studies from the US, France and New Zealand have reported patient eligibility rates of 80 per cent, 86 per cent and 93 per cent respectively. [24][25][26] When examining how many children are eligible for day-case tonsillectomy, it is important to determine the grounds on which they might fail to be eligible.…”
Section: Discussionmentioning
confidence: 99%